2011
DOI: 10.1002/jid.1783
|View full text |Cite
|
Sign up to set email alerts
|

Do Exports Explain Industrial Agglomeration and Regional Disparities in Turkey?

Abstract: Along with an increasing integration with global goods and services markets, regional centres of industrial development have emerged in Turkey. Global linkages may play an important role in regional disparities in a developing country like Turkey through the determination of the locations of industries. This paper examines to what extent global linkages, operationalised by export performance, impact on agglomeration economies and regional disparities in industrial production and industrial employment in Turkey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…[22] used panel data from 1987 to 2001 to explore the influencing factors of industrial agglomeration in China, indicating that economic openness promotes the spatial agglomeration of Chinese industry, while opening up is influenced by geographical and historical factors. [23] uses urban-level employment and production data to find that trade openness has a positive impact on population spatial agglomeration. [24] using the difference between the real wage variable region as a measure of regional agglomeration, which has also been a positive correlation.…”
Section: Empirical Researchmentioning
confidence: 99%
“…[22] used panel data from 1987 to 2001 to explore the influencing factors of industrial agglomeration in China, indicating that economic openness promotes the spatial agglomeration of Chinese industry, while opening up is influenced by geographical and historical factors. [23] uses urban-level employment and production data to find that trade openness has a positive impact on population spatial agglomeration. [24] using the difference between the real wage variable region as a measure of regional agglomeration, which has also been a positive correlation.…”
Section: Empirical Researchmentioning
confidence: 99%
“…They find that transport networks have exerted a positive impact on industry agglomeration, but the magnitude and significance of regression results varied across different industries. Akkemik et al 25 confirmed the explanatory power of new trade theory to industrial concentration. Lu et al 26 found that fiscal support and higher human capital are the two main drivers of industry agglomeration.…”
Section: Determinants Of Industry Agglomerationmentioning
confidence: 91%
“…Extralocatities linkages may play an essential role in regional disparities in a developing country by determining the locations of industries (Akkemik & Göksal, 2014). Agglomeration economies portray a phenomenon widely observed throughout Europe, the United States and especially in developing countries (Knorringa & Nadvi, 2016; Lema et al, 2018; Yang et al, 2022).…”
Section: Agglomeration Economies and Municipal Developmentmentioning
confidence: 99%